PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS WORDWALL UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG MATEMATIKA PADA SISWA KELAS 1 SEKOLAH DASAR - Aidhella Tyas Permatasari; Arita Marini; Waluyo Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop interactive learning media based on Wordwall to improve mathematical counting skills among first-grade elementary school students. The research problem focuses on students’ low arithmetic abilities and the lack of engaging learning media suitable for early childhood characteristics. The research method used is Research and Development (R&D) with a quantitative approach using a one-group pretest-posttest design. The research instruments consisted of a 10-item multiple-choice test for pretest and posttest, and a student response questionnaire regarding the use of Wordwall. The sample in this study involved 20 first-grade students from SDN Tengah 07 Jakarta Timur. The media was developed using the Wordwall platform with the